2016
DOI: 10.1590/s1677-5538.ibju.2015.0607
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior abdominal surgery on the outcomes after robotic - assisted laparoscopic radical prostatectomy: single center experience

Abstract: Purpose:To evaluate the influence of prior abdominal surgery on the outcomes after robotic-assisted laparoscopic radical prostatectomy (RALP).Materials and Methods:We retrospectively analyzed patients with prostate cancer who underwent RALP between June 2012 and February 2015 at our institution. Patients with prior abdominal surgery were compared with those without prior surgery while considering the mean total operating, console, and port-insertion times; mean estimated blood loss; positive surgical margin ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The risk of bias in patient selection in 8 clinical trials (29)(30)(31)(32)(33)(34)(35)(36) was assessed using the Cochrane bias risk assessment tool.…”
Section: Results Of Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias in patient selection in 8 clinical trials (29)(30)(31)(32)(33)(34)(35)(36) was assessed using the Cochrane bias risk assessment tool.…”
Section: Results Of Quality Assessmentmentioning
confidence: 99%
“…In the further screening, 68 articles were excluded due to insufficient data, article types, and failure of research design. Finally, 8 papers were included in the analysis (29)(30)(31)(32)(33)(34)(35)(36). Figure 1 is a flowchart that reflects the identification, inclusion, and elimination of publications in the search process.…”
Section: Search Processmentioning
confidence: 99%
“…In our experience, we do not believe that RP should be avoided in selected patients even with the history of abdominal surgery. Some previous literature revealed that prior abdominal surgery does not impact surgical outcomes and complications [ 17 ]. Even, there are potentially risks of injury due to smaller working space, adhesion, and transplanted renal and ureter, the surgery itself is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the impact of prior abdominal intervention on subsequent urologic surgeries [10][11][12]. For example, one study assessing outcomes following partial nephrectomy showed that PAS was associated with higher estimated blood loss [4].…”
Section: Introductionmentioning
confidence: 99%